Cover Picture: Non‐Thermal Plasma Assisted Fabrication of Ultrathin NiCoOx Nanosheets for High‐Performance Supercapacitor (Batteries & Supercaps 11/2022). Issue 11 (13th October 2022) - Gicha, Birhanu Bayissa; Tufa, Lemma Teshome; Goddati, Mahendra; Adhikari, Samir; Gwak, Juyoung; Lee, Jaebeom
Abstract : The Front Cover illustrates exfoliation of bulk NiCoOx layered double hydroxides into few layers of ultrathin nanosheets using a non‐thermal Ar‐plasma exfoliation strategy to obtain a single layer of NiCoOx nanosheets with excellence supercapacitive properties owing to improvement on the accessible active site for charge storage and transport. More information can be found in the Research Article by J. Lee and co‐workers .